A combination of interferon‐gamma and interleukin‐2 production by Coxiella burnetii‐stimulated circulating cells discriminates between chronic Q fever and past Q fever. (18th November 2013) - Schoffelen, T.; Sprong, T.; Bleeker‐Rovers, C. P.; Wegdam‐Blans, M. C. A.; Ammerdorffer, A.; Pronk, M. J. H.; Soethoudt, Y. E. P.; van Kasteren, M. E. E.; Herremans, T.; Bijlmer, H. A.; Netea, M. G.; van der Meer, J. W. M.; et al.
Abstract Infection with Coxiella burnetii may lead to life‐threatening chronic Q fever endocarditis or vascular infections, which are often difficult to diagnose. The present study aims to investigate whether measurement of in‐vitro interferon‐gamma (IFN‐γ) production, a key cytokine in the immune response against C. burnetii, differentiates chronic from a past cleared infection, and whether measurement of other cytokines would improve the discriminative power. First, C. burnetii‐specific IFN‐γ production was measured in whole blood of 28 definite chronic Q fever patients and compared with 135 individuals with past Q fever (seropositive controls) and 908 seronegative controls. IFN‐γ production was significantly higher in chronic Q fever patients than in controls, but with overlapping values between patients and seropositives. Secondly, the production of a series of other cytokines was measured in a subset of patients and controls, which showed that interleukin (IL)‐2 production was significantly lower in patients than in seropositive controls. Subsequently, measuring IL‐2 in all patients and all controls with substantial IFN‐γ production showed that an IFN‐γ/IL‐2 ratio >11 had a sensitivity and specificity of 79% and 96%, respectively, to diagnose chronic Q fever. This indicates that a high IFN‐γ/IL‐2 ratio is highly suggestive for chronic Q fever. In an additional group of 25 individuals with persistent high anti‐Coxiella phase I IgG titres without definite chronic infection, all but six showed an IFN‐γ/IL‐2 ratio <11. In conclusion, these findings hold promise for the often difficult diagnostic work‐up of Q fever and the IFN‐γ/IL‐2 ratio may be used as an additional diagnostic marker.